Positive plate and lithium ion battery
By modifying the combination of lithium cobalt oxide positive electrode material and specific dispersant, the problem of poor durability of lithium-ion batteries at high voltages is solved, and higher cycle stability and safety are achieved.
Patent Information
- Application Number
- CN202411987094.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Existing lithium-ion batteries have poor durability at high voltages, low cycle life, and poor migration mechanics of the negative electrode material, which poses safety risks.
The modified lithium cobalt oxide positive electrode material is used, and the positive electrode dispersant of fluorinated acrylate rubber and hydrogenated nitrile rubber is combined. Through a specific preparation method and combination of additives, the high pressure resistance and cycle stability of the positive electrode sheet are improved.
It significantly improves the cycling stability and safety of lithium-ion batteries at high voltages, extends the battery life, and reduces the risk of dispersant decomposition and gas production at high voltages.
Smart Images

Figure BDA0005224077180000101 
Figure BDA0005224077180000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a positive electrode sheet and a lithium-ion battery. Background Art
[0002] Lithium cobalt oxide cathode materials have outstanding performance in energy density due to their outstanding high compaction density. They have excellent cycle and safety performance, making them widely used in batteries for consumer products and occupying a dominant position. With the market's increasingly high battery life requirements for portable devices, it means that the energy density of the battery cell needs to be further improved without increasing the volume of the battery cell.
[0003] Lithium cobalt oxide with a charging cut-off voltage of 4.2V can only play 1 / 2 of its theoretical capacity in practical applications (theoretical capacity 270mAh·g -1 ), only half of Li + Therefore, further increasing the cut-off voltage can increase the Li + The utilization rate means increasing the amount of electricity, which is an effective way to increase the energy density of lithium cobalt oxide. + A large amount of oxygen is released from lithium cobalt oxide, causing the lithium cobalt oxide structure to collapse on a large scale, thereby losing the ability to deintercalate and deintercalate lithium, resulting in rapid capacity decay and low cycle life. Therefore, the application of high-voltage lithium-ion batteries with lithium cobalt oxide positive electrodes requires solving problems such as lithium cobalt oxide structural stability, oxygen defects, and cobalt dissolution under high voltage.
[0004] In addition, the negative electrode material of lithium-ion batteries can also determine the performance of high-voltage lithium-ion batteries; untreated graphite negative electrodes have poor lithium ion migration kinetics and are prone to lithium deposition during high-current charging, posing a safety hazard; the negative electrode graphite has low compaction and gram capacity and cannot contribute to volume energy density.
[0005] It can be seen that the existing lithium-ion battery material system cannot meet the requirements of lithium-ion batteries for cycle life and charging speed under high voltage (≥4.48V). Therefore, it is of great significance to improve the existing lithium cobalt oxide positive electrode battery material system and improve the structural stability of lithium cobalt oxide under high voltage and long cycle to meet the battery fast charging requirements. Summary of the invention
[0006] The main purpose of the present application is to provide a positive electrode sheet and a lithium-ion battery to solve the problem of poor high voltage resistance of lithium-ion batteries in the prior art.
[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a positive electrode sheet is provided, including a current collector and a positive electrode active layer, the material of the positive electrode active layer includes lithium cobalt oxide, a positive electrode dispersant, a positive electrode conductor and a positive electrode binder; wherein the positive electrode dispersant includes fluorinated acrylate rubber.
[0008] Furthermore, the above-mentioned positive electrode dispersant also includes hydrogenated nitrile rubber; further, the mass proportion of hydrogenated segments in the hydrogenated nitrile rubber is 3 to 9%; and / or, the mass proportion of fluorinated segments in the fluorinated acrylate rubber is 3 to 9%; and / or, the weight average molecular weight of the hydrogenated nitrile rubber is 10,000 to 700,000 g / mol; and / or, the weight average molecular weight of the fluorinated acrylate rubber is 5,000 to 200,000 g / mol.
[0009] Furthermore, the positive electrode dispersant is a combination of hydrogenated nitrile rubber and fluorinated acrylate rubber, and the mass ratio of hydrogenated nitrile rubber to fluorinated acrylate rubber is 1 to 20:1.
[0010] Furthermore, the mass ratio of the above-mentioned lithium cobalt oxide, positive electrode dispersant, positive electrode conductive agent, and positive electrode binder is (96-99):(0.01-0.1):(0.5-1.5):(0.5-1.5).
[0011] Further, the above-mentioned lithium cobalt oxide is modified lithium cobalt oxide; further, the preparation method of the modified lithium cobalt oxide comprises: step S1, mixing raw materials including a first cobalt salt and a first aluminum salt, and then sequentially performing a first coprecipitation and a first heat treatment to obtain a first aluminum-doped cobalt tetroxide; step S2, mixing raw materials including a second cobalt salt and a second aluminum salt, and then sequentially performing a second coprecipitation and a second heat treatment to obtain a second aluminum-doped cobalt tetroxide; step S3, mixing a raw material including a first lithium source, a first aluminum-doped cobalt tetroxide and a first additive The raw materials are mixed and subjected to a first calcination to obtain a first lithium cobaltate; step S4, the raw materials including a second lithium source, a second aluminum-doped cobalt oxide and a second additive are mixed and subjected to a second calcination to obtain a second lithium cobaltate; step S5, the raw materials including the first lithium cobaltate, the second lithium cobalt oxide and a third additive are mixed and subjected to a third calcination to obtain a modified lithium cobaltate; wherein the median particle size of the first aluminum-doped cobalt oxide is 3 to 5 μm; and / or the median particle size of the second aluminum-doped cobalt oxide is 15 to 18 μm.
[0012] Further, in the above step S1, the mass ratio of the first cobalt salt to the first aluminum salt is 1:0.005-0.015; and / or, the temperature of the first coprecipitation is 25-45°C; and / or, the time of the first coprecipitation is 10-18h; and / or, the temperature of the first heat treatment is 600-800°C; and / or, the time of the first heat treatment is 4-8h; and / or, in step S2, the mass ratio of the second cobalt salt to the second aluminum salt is 1:0.005-0.015; and / or, the temperature of the second coprecipitation is 25-45°C; and / or, the time of the second coprecipitation is 10-18h; and / or, the temperature of the second heat treatment is 600-800°C; and / or, the time of the second heat treatment is 3-6h.
[0013] Further, in the above step S3, the mass ratio of the first lithium source, the first aluminum-doped cobalt tetroxide and the first additive is 1:(2.1-2.5):(0.005-0.01); and / or the temperature of the first calcination is 700-1000°C; and / or the time of the first calcination is 6-10h; and / or, in step S4, the mass ratio of the second lithium source, the second aluminum-doped cobalt tetroxide and the second additive is 1:(2.1-2.5):(0.005-0.01); and / or the temperature of the second calcination is 700-900°C; and / or the time of the second calcination is 6-10h.
[0014] Furthermore, in the above step S5, the mass ratio of the first lithium cobaltate, the second lithium cobaltate and the third additive is 1:(0.2-0.3):(0.005-0.01); and / or, the temperature of the third calcination is 400-600° C.; and / or, the time of the third calcination is 4-6 hours.
[0015] Further, the above-mentioned first additive and second additive are each independently selected from any one or more of a first Mg source, a first Al source, a first Co source, a first Ti source, a first Zr source, a first Y source and a first La source; and / or, the third additive is selected from any one or more of a second Mg source, a second Al source, a second Ti source, a second Zr source, a second Y source, a second La source, a P source, a F source and a second Co source; further, the first additive is a combination of a first Mg source and a first Y source, and the mass ratio of the first Mg source to the first Y source is 1:0.1 to 0.5; and / or, the second additive is a combination of a first Co source and a first Ti source, and the mass ratio of the first Co source to the first Ti source is 1:0.1 to 1; and / or, the third additive is a combination of a second Al source and a F source, and the mass ratio of the second Al source to the F source is 1:0.1 to 1.
[0016] According to another aspect of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet mentioned above.
[0017] By applying the technical solution of the present application, the fluorinated acrylate rubber can provide good dispersion stability in the slurrying process of the positive electrode material. During the charge and discharge process of the positive electrode sheet, the fluorinated acrylate rubber is not easy to decompose under high voltage. The presence of the fluorinated acrylate rubber not only helps to improve the dispersibility of each component, but also helps to improve the high voltage resistance of the positive electrode sheet. In addition, the fluoride ion itself is inert. Even if oxidative decomposition occurs, the carbon fluoride formed is difficult to be oxidized in one step, which helps to further reduce the risk of gas production. Therefore, the dispersant containing fluorinated acrylate rubber in the positive electrode sheet helps to reduce the risk of decomposition and gas production of the dispersant under high voltage, thereby helping to improve the high voltage resistance of the positive electrode sheet, and then helping to improve the safety and electrochemical performance of the battery under high voltage. DETAILED DESCRIPTION
[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below in conjunction with the embodiments.
[0019] As analyzed in the background technology of the present application, lithium-ion batteries in the prior art have the problem of poor high voltage resistance. In order to solve this problem, the present application provides a positive electrode sheet and a lithium-ion battery.
[0020] In a typical embodiment of the present application, a positive electrode sheet is provided, including a current collector and a positive electrode active layer, wherein the material of the positive electrode active layer includes lithium cobalt oxide, a positive electrode dispersant, a positive electrode conductor and a positive electrode binder; wherein the positive electrode dispersant includes fluorinated acrylate rubber.
[0021] Fluorinated acrylate rubber can provide good dispersion stability during the slurrying process of the positive electrode material. During the charge and discharge process of the positive electrode sheet, fluorinated acrylate rubber is not easy to decompose under high voltage. The presence of fluorinated acrylate rubber not only helps to improve the dispersibility of each component, but also helps to improve the high voltage resistance of the positive electrode sheet. In addition, the fluoride ion itself is inert. Even if oxidative decomposition occurs, the carbon fluoride formed is difficult to be oxidized in one step, which helps to further reduce the risk of gas production. Therefore, the dispersant containing fluorinated acrylate rubber in the positive electrode sheet helps to reduce the risk of decomposition and gas production of the dispersant under high voltage, thereby helping to improve the high voltage resistance of the positive electrode sheet, and then helping to improve the safety and electrochemical performance of the battery under high voltage.
[0022] In order to further improve the high-voltage resistance of the positive electrode sheet, in one embodiment of the present application, the above-mentioned positive electrode dispersant also includes hydrogenated nitrile rubber; in one embodiment of the present application, the mass proportion of the hydrogenated segment in the hydrogenated nitrile rubber is 3-9%; and / or, the mass proportion of the fluorinated segment in the fluorinated acrylate rubber is 3-9%; and / or, the weight-average molecular weight of the hydrogenated nitrile rubber is 10,000-700,000 g / mol; and / or, the weight-average molecular weight of the fluorinated acrylate rubber is 5,000-200,000 g / mol.
[0023] The hydrogenated nitrile rubber and fluorinated acrylate rubber can be purchased from Shenzhen Haodian Technology Co., Ltd. or Ruiong Co., Ltd.
[0024] In one embodiment of the present application, the positive electrode dispersant is a combination of hydrogenated nitrile rubber and fluorinated acrylate rubber, and the mass ratio of hydrogenated nitrile rubber to fluorinated acrylate rubber is 1 to 20:1.
[0025] Hydrogenated nitrile rubber and fluorinated acrylate rubber have different rheological properties. Controlling the mass ratio of hydrogenated nitrile rubber and fluorinated acrylate rubber within the above range helps to optimize the rheological properties of the slurry, so that it can maintain better stability and uniformity during stirring and coating. Hydrogenated nitrile rubber and fluorinated acrylate rubber each have unique high-voltage resistance properties. Hydrogenated nitrile rubber reduces unsaturated double bonds and improves oxidation stability through hydrogenation; fluorinated acrylate rubber increases the electronegativity of the material and reduces double bond activity through fluorinated chain segments. Mixing the two in the above ratio helps to improve the synergistic effect between the two, thereby helping to improve the stability of the dispersant in a high-voltage environment and reduce the risk of decomposition and gas production of the dispersant.
[0026] In one embodiment of the present application, the mass ratio of the above-mentioned lithium cobalt oxide, positive electrode dispersant, positive electrode conductor, and positive electrode binder is (96-99):(0.01-0.1):(0.5-1.5):(0.5-1.5).
[0027] Lithium cobalt oxide is the active ingredient in the positive electrode material, responsible for the embedding and de-embedding of lithium ions during the charge and discharge process of the battery. Although too much positive dispersant content helps to improve the stability of the positive electrode slurry, it will affect the migration rate of lithium ions; too little positive dispersant content cannot play a good dispersing role and affect the coating quality. Controlling the mass ratio of lithium cobalt oxide, positive dispersant, positive conductive agent, and positive binder within the above range will help improve the rate performance and cycle stability of the positive electrode sheet at high voltage.
[0028] In one embodiment of the present application, the above-mentioned lithium cobalt oxide is modified lithium cobalt oxide; in one embodiment of the present application, the preparation method of the modified lithium cobalt oxide comprises: step S1, mixing raw materials including a first cobalt salt and a first aluminum salt, and then sequentially performing a first coprecipitation and a first heat treatment to obtain a first aluminum-doped cobalt tetroxide; step S2, mixing raw materials including a second cobalt salt and a second aluminum salt, and then sequentially performing a second coprecipitation and a second heat treatment to obtain a second aluminum-doped cobalt tetroxide; step S3, mixing raw materials including a first lithium source, a first aluminum-doped cobalt tetroxide, and a second aluminum-doped cobalt tetroxide; and the raw material of the first additive, and then perform a first calcination to obtain a first lithium cobaltate; step S4, mix the raw material including the second lithium source, the second aluminum-doped cobalt tetroxide and the second additive, and then perform a second calcination to obtain a second lithium cobaltate; step S5, mix the raw materials including the first lithium cobaltate, the second lithium cobaltate and the third additive, and then perform a third calcination to obtain a modified lithium cobaltate; wherein the median particle size of the first aluminum-doped cobalt tetroxide is 3 to 5 μm; and / or the median particle size of the second aluminum-doped cobalt tetroxide is 15 to 18 μm.
[0029] By adding aluminum in the cobalt oxide precursor stage, it helps to stabilize the layered structure of lithium cobalt oxide and reduce the structural damage caused by the deintercalation of a large amount of lithium at high voltage. The addition of aluminum helps to inhibit the occurrence of irreversible phase change, improve the cycle stability of the material at high voltage, and reduce capacity decay and structural collapse. The addition of the first additive and the second additive helps to improve the structural stability of lithium cobalt oxide, promote the growth of lithium cobalt oxide crystals, and improve the conductivity of lithium cobalt oxide. The addition of the third additive helps to form a solid solution on the surface of lithium cobalt oxide, repair the surface of lithium cobalt oxide, improve the structural stability of excessive delithiation of lithium cobalt oxide interface, and reduce the direct contact of electrolyte with positive electrode materials. Controlling the median particle size of the first aluminum-doped cobalt oxide and the median particle size of the second aluminum-doped cobalt oxide within the above range helps to improve the compaction density of lithium cobalt oxide, thereby helping to further improve the stability of the positive electrode sheet at high voltage.
[0030] In one embodiment of the present application, in the above-mentioned step S1, the mass ratio of the first cobalt salt to the first aluminum salt is 1:0.005-0.015; and / or, the temperature of the first coprecipitation is 25-45°C; and / or, the time of the first coprecipitation is 10-18h; and / or, the temperature of the first heat treatment is 600-800°C; and / or, the time of the first heat treatment is 4-8h; and / or, in step S2, the mass ratio of the second cobalt salt to the second aluminum salt is 1:0.005-0.015; and / or, the temperature of the second coprecipitation is 25-45°C; and / or, the time of the second coprecipitation is 10-18h; and / or, the temperature of the second heat treatment is 600-800°C; and / or, the time of the second heat treatment is 3-6h.
[0031] Controlling the mass ratio of the first cobalt salt to the first aluminum salt, and the mass ratio of the second cobalt salt to the second aluminum salt within the above range helps control the doping amount of aluminum element, thereby helping to improve the structural stability of lithium cobalt oxide. Controlling the temperature and time of the first coprecipitation, and the temperature and time of the second coprecipitation within the above range helps control the size of aluminum-doped cobalt oxide within a suitable range, thereby helping to improve the compaction density of lithium cobalt oxide. Controlling the temperature and time of the first heat treatment, and the temperature and time of the second heat treatment within the above range helps to improve the crystallinity of aluminum-doped cobalt oxide, thereby helping to improve the conductivity of lithium cobalt oxide.
[0032] In one embodiment of the present application, in the above-mentioned step S3, the mass ratio of the first lithium source, the first aluminum-doped cobalt tetroxide and the first additive is 1:(2.1-2.5):(0.005-0.01); and / or, the temperature of the first calcination is 700-1000°C; and / or, the time of the first calcination is 6-10h; and / or, in step S4, the mass ratio of the second lithium source, the second aluminum-doped cobalt tetroxide and the second additive is 1:(2.1-2.5):(0.005-0.01); and / or, the temperature of the second calcination is 700-900°C; and / or, the time of the second calcination is 6-10h.
[0033] Controlling the mass ratio of the first lithium source, the first aluminum-doped cobalt oxide and the first additive, and the mass ratio of the second lithium source, the second aluminum-doped cobalt oxide and the second additive within the above range is helpful to form lithium cobalt oxide with a stable structure and low impurity content. Too high a calcination temperature may cause sintering of the material and affect the migration channel of lithium ions; too low a temperature may not be able to complete a full lithiation reaction. Controlling the temperature and time of the first calcination and the temperature and time of the second calcination within the above range is helpful to improve the crystallinity of lithium cobalt oxide, thereby helping to improve the cycle stability of the positive electrode sheet under high voltage.
[0034] In one embodiment of the present application, the step S3 further comprises crushing and sieving the product after the first calcination in sequence to obtain the first lithium cobalt oxide with a median particle size of 16 to 18 μm.
[0035] In one embodiment of the present application, the step S4 further comprises crushing and sieving the product after the second calcination in sequence to obtain a second lithium cobalt oxide with a median particle size of 3 to 5 μm.
[0036] In one embodiment of the present application, in the above step S5, the mass ratio of the first lithium cobaltate, the second lithium cobaltate and the third additive is 1:(0.2-0.3):(0.005-0.01); and / or, the temperature of the third calcination is 400-600°C; and / or, the time of the third calcination is 4-6h.
[0037] Controlling the mass ratio of the first lithium cobalt oxide, the second lithium cobalt oxide and the third additive within the above range is helpful to form a composite modified layer, reduce the direct contact between the electrolyte and the active material, inhibit side reactions, and help enhance the migration kinetics of lithium ions, improve the conductivity and cycle life of the material. Controlling the temperature and time of the third calcination within the above range is helpful to promote the chemical reaction between the third additive and the lithium cobalt oxide, form a solid solution on the surface of the lithium cobalt oxide, and help improve the structure and electrochemical properties of the material.
[0038] In one embodiment of the present application, the above step S5 further includes crushing and sieving the product after the third calcination in sequence to obtain modified lithium cobalt oxide with a median particle size of 14 to 17 μm.
[0039] In one embodiment of the present application, the first additive and the second additive are each independently selected from any one or more of a first Mg source, a first Al source, a first Co source, a first Ti source, a first Zr source, a first Y source and a first La source; and / or, the third additive is selected from any one or more of a second Mg source, a second Al source, a second Ti source, a second Zr source, a second Y source, a second La source, a P source, a F source and a second Co source; in one embodiment of the present application, the first additive is a combination of a first Mg source and a first Y source, and the mass ratio of the first Mg source to the first Y source is 1:0.1 to 0.5; and / or, the second additive is a combination of a first Co source and a first Ti source, and the mass ratio of the first Co source to the first Ti source is 1:0.1 to 1; and / or, the third additive is a combination of a second Al source and a F source, and the mass ratio of the second Al source to the F source is 1:0.1 to 1.
[0040] Controlling the types of the first additive, the second additive, and the third additive within the above range helps to further improve the cycle stability of the positive electrode material under high voltage while enriching the material selectivity. The first additive is a combination of the first Mg source and the first Y source. The Mg element and the Y element can form a structure that is conducive to lithium ion diffusion and electron transmission during the doping process, and the Mg element and the Y element help stabilize the crystal structure of lithium cobalt oxide and inhibit harmful phase changes and oxygen precipitation under high voltage. The second additive is a combination of the first Co source and the first Ti source. The Co element can repair the structural defects on the surface of lithium cobalt oxide and consume residual lithium on the surface. At the same time, the added Ti element can inhibit the further growth of lithium cobalt oxide crystals during secondary sintering; the third additive is a combination of the second Al source and the F source. The temperature of the third calcination is relatively low, and the Al element coated on the surface is not easy to diffuse to the inner layer, so it plays a role in stabilizing the structure on the surface; the presence of the F element replaces the oxygen position in the lithium cobalt oxide, which helps to inhibit oxygen release during the phase change process.
[0041] Including but not limited to, the first Mg source and the second Mg source are independently selected from any one or more of MgO, MgF2 and Mg(OH)2;
[0042] Including but not limited to, the first Al source and the second Al source are each independently Al2O3 and / or AlF3;
[0043] Including but not limited to, the first Ti source and the second Ti source are each independently TiO2 and / or Ti2O3;
[0044] Including but not limited to, the first Zr source and the second Zr source are independently selected from any one or more of ZrO2, Zr(OH)4 and ZrF4;
[0045] Including but not limited to, the first Y source and the second Y source are each independently Y2O3;
[0046] Including but not limited to, the first La source and the second La source are independently selected from any one or more of La2O3, La2(CO3)3, La(OH)3 and LaF3;
[0047] Including but not limited to, the above-mentioned P source is selected from any one or more of P2O3, NH4H2PO4 and (NH4)2HPO4;
[0048] Including but not limited to, the above-mentioned F source is NH4HF2;
[0049] Including but not limited to, the first Co source and the second Co source are each independently Co(OH)2 and / or Co3O4;
[0050] Including but not limited to, the first cobalt salt and the second cobalt salt are independently selected from any one or more of Co(NO3)2, CoCl2 and CoSO4;
[0051] Including but not limited to, the first aluminum salt and the second aluminum salt are independently selected from any one or more of Al(NO3)3, AlCl3 and Al2(SO4)3;
[0052] Including but not limited to, the first lithium source and the second lithium source are independently selected from any one or more of LiOH, Li2CO3, LiNO3 and CH3COOLi.
[0053] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet mentioned above.
[0054] Since the lithium-ion battery contains the positive electrode sheet of the present application, the lithium-ion battery has excellent cycle stability at high voltage.
[0055] In one embodiment of the present application, the above-mentioned negative electrode sheet includes a current collector and a negative electrode active layer, and the materials of the negative electrode active layer include a negative electrode active material, a negative electrode conductive agent, a negative electrode dispersant and a negative electrode binder; in one embodiment of the present application, the mass ratio of the negative electrode active material, the negative electrode conductive agent, the negative electrode dispersant and the negative electrode binder is (95~99):(0.1~1.5):(0.5~1.5):(0.5~1.5).
[0056] Including but not limited to, the above-mentioned negative electrode active material is carbon-coated graphite and / or silicon-based graphite; the negative electrode active material is carbon-coated graphite, which can meet the fast charging capability of the battery; the negative electrode active material is silicon-based negative electrode graphite, which helps to further improve the energy density of the battery.
[0057] Including but not limited to, the above-mentioned negative electrode dispersant is sodium carboxymethyl cellulose and / or lithium carboxymethyl cellulose;
[0058] Including but not limited to the above-mentioned negative electrode binder polystyrene butadiene and / or polyacrylic acid;
[0059] Including but not limited to, the positive electrode conductive agent and the negative electrode conductive agent are independently selected from any one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene.
[0060] The preparation method of the above-mentioned lithium-ion battery includes: step 1: weigh the positive electrode binder according to the measurement and dissolve it in N-methylpyrrolidone to obtain the positive electrode glue, add the measured amount of lithium cobalt oxide, positive electrode dispersant, and positive electrode conductive agent to the positive electrode glue, stir, and obtain the positive electrode slurry; weigh the negative electrode dispersant according to the measurement and dissolve it in deionized water to obtain the negative electrode glue, take out 25% to 35% of the negative electrode glue and add the measured amount of negative electrode active material to knead, add the remaining negative electrode glue, negative electrode binder and negative electrode conductive agent, stir, and obtain the negative electrode slurry. Step 2: The positive electrode slurry and the negative electrode slurry are uniformly coated on the positive electrode collector and the negative electrode collector respectively according to the requirements of the coating structure, and roll, slit, ear welding, and glue are performed to obtain the positive electrode sheet and the negative electrode sheet; the coating structure includes single-layer coating and double-layer coating. Step three, the positive electrode sheet and the negative electrode sheet are separated by a separator, stacked or wound to form a bare battery cell and packaged, and then vacuum-baked, injected with electrolyte, left to stand, high-temperature pressure-formed, evacuated and packaged, capacity divided, and tested to obtain a lithium-ion battery.
[0061] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0062] Example 1
[0063] 1) Preparation of modified lithium cobalt oxide:
[0064] Co(NO3)2 and Al(NO3)3 are dissolved in deionized water at a mass ratio of 1:0.005, and a first coprecipitation and a first heat treatment are carried out in sequence. After crushing, a first aluminum-doped cobalt oxide with a median particle size of 3 μm is obtained. The temperature of the first coprecipitation is 25°C, the time of the first coprecipitation is 18 hours, the temperature of the first heat treatment is 600°C, and the time of the first heat treatment is 8 hours. Step S2: CoCl2 and AlCl3 are dissolved in deionized water at a mass ratio of 1:0.005, and a second coprecipitation and a second heat treatment are carried out in sequence. After crushing, a second aluminum-doped cobalt oxide with a median particle size of 15 μm is obtained. The temperature of the second coprecipitation is 25°C, the time of the second coprecipitation is 18 hours, the temperature of the second heat treatment is 600°C, and the time of the second heat treatment is 6 hours. Step S3: LiOH, the first aluminum-doped cobalt oxide and the first additive are mixed and first calcined to obtain a first lithium cobaltate. The first additive is MgO and Y2O3 in a mass ratio of 1:0.1. The mass ratio of LiOH, the first aluminum-doped cobalt oxide and the first additive is 1:2.1:0.01, the temperature of the first calcination is 700°C, and the time of the first calcination is 10h; step S4, mixing Li2CO3, the second aluminum-doped cobalt oxide and the second additive and performing a second calcination to obtain a second lithium cobaltate, the second additive is Co(OH)2 and TiO2 in a mass ratio of 1:0.1, the mass ratio of Li2CO3, the second aluminum-doped cobalt oxide and the second ... mass ratio of Li2CO3, the second aluminum-doped cobalt oxide and the second additive is 1:2.1:0.01, the mass ratio of Li2CO3, the second aluminum-doped cobalt oxide and the second additive is 1:2.1:0.01, the mass ratio of Li2CO3, the second aluminum-doped cobalt oxide and the second additive is 1:2.1:0.01, the mass ratio of Li2CO3, the second aluminum-doped cobalt oxide and the second additive is 1:2.1:0.01, the mass ratio of Li2CO3, the second aluminum-doped cobalt oxide and the second additive is 1:2.1:0.01, the mass ratio of Li2CO3, the second aluminum-doped cobalt oxide and the second additive is The ratio of the first cobalt oxide to the second cobalt oxide is 1:2.1:0.01, the temperature of the second calcination is 700°C, and the time of the second calcination is 10 hours; step S5, mixing the first lithium cobalt oxide, the second lithium cobalt oxide and the third additive and then performing a third calcination to obtain modified lithium cobalt oxide, the third additive is Al2O3 and NH4HF2 in a mass ratio of 1:0.1, the mass ratio of the first lithium cobalt oxide, the second lithium cobalt oxide and the third additive is 1:0.2:0.01, the temperature of the third calcination is 400°C, and the time of the third calcination is 6 hours.
[0065] 2) Preparation of positive electrode sheet:
[0066] The positive electrode binder is added to N-methylpyrrolidone and mixed to obtain a glue solution with a mass concentration of 7% of the positive electrode binder. The modified lithium cobalt oxide, positive electrode conductive agent and positive electrode dispersant are added to the glue solution and stirred to obtain a positive electrode slurry. The mass ratio of the modified lithium cobalt oxide, the positive electrode dispersant, the positive electrode conductive agent and the positive electrode binder is 98:0.02:1.18:0.8. The dispersant is hydrogenated nitrile rubber and fluorinated acrylate rubber of Shenzhen Haodian Technology Co., Ltd. The weight average molecular weight of the hydrogenated nitrile rubber is 10000g / mol, the weight average molecular weight of the fluorinated acrylate rubber is 5000g / mol, the mass proportion of the hydrogenated segment in the hydrogenated nitrile rubber is 6%, the mass proportion of the fluorinated segment in the fluorinated acrylate rubber is 6%, the mass ratio of the hydrogenated nitrile rubber to the fluorinated acrylate rubber is 10:1, and the positive electrode conductive agent is conductive carbon black. The positive electrode slurry is evenly coated on both sides of the aluminum foil, and the positive electrode sheet is obtained after baking, rolling, die-cutting, tab welding and gluing.
[0067] Example 2
[0068] The difference from Example 1 is that the mass proportion of the hydrogenated segment in the hydrogenated nitrile rubber is 3%, and the mass proportion of the fluorinated segment in the fluorinated acrylate rubber is 9%, and finally a positive electrode sheet is obtained.
[0069] Example 3
[0070] The difference from Example 1 is that the mass proportion of the hydrogenated segment in the hydrogenated nitrile rubber is 9%, and the mass proportion of the fluorinated segment in the fluorinated acrylate rubber is 3%, and finally a positive electrode sheet is obtained.
[0071] Example 4
[0072] The difference from Example 1 is that the mass proportion of the hydrogenated segment in the hydrogenated nitrile rubber is 2%, and the mass proportion of the fluorinated segment in the fluorinated acrylate rubber is 2%, and finally a positive electrode sheet is obtained.
[0073] Example 5
[0074] The difference from Example 1 is that the weight average molecular weight of the hydrogenated nitrile rubber is 700,000 g / mol, and the weight average molecular weight of the fluorinated acrylate rubber is 200,000 g / mol, and finally a positive electrode sheet is obtained.
[0075] Example 6
[0076] The difference from Example 1 is that the weight average molecular weight of the hydrogenated nitrile rubber is 1,000,000 g / mol, and the weight average molecular weight of the fluorinated acrylate rubber is 300,000 g / mol, and finally a positive electrode sheet is obtained.
[0077] Example 7
[0078] The difference from Example 1 is that the mass ratio of hydrogenated nitrile rubber to fluorinated acrylate rubber is 20:1, and a positive electrode sheet is finally obtained.
[0079] Example 8
[0080] The difference from Example 1 is that the mass ratio of hydrogenated nitrile rubber to fluorinated acrylate rubber is 1:1, and a positive electrode sheet is finally obtained.
[0081] Example 9
[0082] The difference from Example 1 is that the hydrogenated nitrile rubber is eliminated, and a positive electrode sheet is finally obtained.
[0083] Example 10
[0084] The difference from Example 1 is that the mass ratio of modified lithium cobalt oxide, positive electrode dispersant, positive electrode conductive agent and positive electrode binder is 96:0.1:0.5:1.5, and finally a positive electrode sheet is obtained.
[0085] Embodiment 11
[0086] The difference from Example 1 is that the mass ratio of modified lithium cobalt oxide, positive electrode dispersant, positive electrode conductive agent and positive electrode binder is 99:0.01:1.5:0.5, and finally a positive electrode sheet is obtained.
[0087] Example 12
[0088] The difference from Example 1 is that the mass ratio of modified lithium cobalt oxide, positive electrode dispersant, positive electrode conductive agent and positive electrode binder is 99:0.005:2:0.3, and finally a positive electrode sheet is obtained.
[0089] Example 13
[0090] The difference from Example 1 is that the mass ratio of LiOH, the first aluminum-doped cobalt tetroxide and the first additive is 1:2.5:0.005, the mass ratio of Li2CO3, the second aluminum-doped cobalt tetroxide and the second additive is 1:2.5:0.005, and the mass ratio of the first lithium cobaltate, the second lithium cobaltate and the third additive is 1:0.3:0.005, and finally a positive electrode sheet is obtained.
[0091] Embodiment 14
[0092] The difference from Example 1 is that the mass ratio of LiOH, the first aluminum-doped cobalt tetroxide and the first additive is 1:1.5:0.01, the mass ratio of Li2CO3, the second aluminum-doped cobalt tetroxide and the second additive is 1:1.5:0.01, and the mass ratio of the first lithium cobaltate, the second lithium cobaltate and the third additive is 1:1.5:0.01, and finally a positive electrode sheet is obtained.
[0093] Embodiment 15
[0094] The difference from Example 1 is that the first additive is MgO and Y2O3 in a mass ratio of 1:0.5, the second additive is Co(OH)2 and TiO2 in a mass ratio of 1:1, and the third additive is Al2O3 and NH4HF2 in a mass ratio of 1:1, and finally a positive electrode sheet is obtained.
[0095] Example 16
[0096] The difference from Example 1 is that the first additive is MgO and Y2O3 in a mass ratio of 1:0.05, the second additive is Co(OH)2 and TiO2 in a mass ratio of 1:0.05, and the third additive is Al2O3 and NH4HF2 in a mass ratio of 1:0.05, and finally a positive electrode sheet is obtained.
[0097] Comparative Example 1
[0098] The difference from Example 1 is that the positive electrode dispersant is polyvinyl pyrrolidone, and a positive electrode sheet is finally obtained.
[0099] Preparation of negative electrode:
[0100] The mass ratio of carbon-coated graphite, graphene, sodium carboxymethyl cellulose and polystyrene butadiene is 97:0.4:1.1:1.5. Sodium carboxymethyl cellulose is added to deionized water to disperse into a glue solution, carbon-coated graphite and graphene are added to the glue solution and stirred, and then sodium carboxymethyl cellulose is added to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on both sides of the copper foil, and the negative electrode sheet is obtained after baking, rolling, die-cutting, pole ear welding, and gluing.
[0101] Preparation of the battery:
[0102] The positive electrode sheet, separator and negative electrode sheet prepared in the embodiment and comparative example are stacked in order to obtain a bare battery cell, which is packaged with an aluminum-plastic film of suitable size, baked, and injected with electrolyte. After standing at high temperature, high-temperature and high-pressure formation, vacuum sealing and capacity separation are performed to obtain a high-voltage lithium cobalt oxide battery.
[0103] Performance Testing
[0104] Capacity retention after 500 cycles at 45°C: After placing the battery in a 45°C oven for 2 hours, perform the following charge and discharge cycles for 500 weeks: 1C constant current charge to 4.53V, constant voltage to 0.05C stop; leave for 10 minutes; 0.7C discharge to 3.0V, leave for 10 minutes.
[0105] The amount of cobalt dissolved from the negative electrode after 500 cycles at 45°C: The negative electrode sheet was disassembled from the battery after 500 cycles and baked in an oven at 45°C for 6 h. The baked electrode sheet was punched using a circular punching machine (fixed area 5.02 cm 2) The discs are weighed and then acid digested. After diluting to the cobalt working curve range of 10ppm to 2000ppm, the Co element is determined by ICP-OES. This value is the cobalt content dissolved from the positive electrode to the negative electrode.
[0106] The capacity retention rate of the lithium cobalt oxide battery prepared above and the amount of cobalt dissolution from the negative electrode were tested after 500 cycles at 45°C. The test results are shown in Table 1.
[0107] Table 1
[0108]
[0109]
[0110] From the above description, it can be seen that the above embodiments of the present application achieve the following technical effects:
[0111] Fluorinated acrylate rubber can provide good dispersion stability during the slurrying process of the positive electrode material. During the charge and discharge process of the positive electrode sheet, fluorinated acrylate rubber is not easy to decompose under high voltage. The presence of fluorinated acrylate rubber not only helps to improve the dispersibility of each component, but also helps to improve the high voltage resistance of the positive electrode sheet. In addition, the fluoride ion itself is inert. Even if oxidative decomposition occurs, the carbon fluoride formed is difficult to be oxidized in one step, which helps to further reduce the risk of gas production. Therefore, the dispersant containing fluorinated acrylate rubber in the positive electrode sheet helps to reduce the risk of decomposition and gas production of the dispersant under high voltage, thereby helping to improve the high voltage resistance of the positive electrode sheet, and then helping to improve the safety and electrochemical performance of the battery under high voltage.
[0112] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A positive electrode sheet, comprising a current collector and a positive electrode active layer, characterized in that: The material of the positive electrode active layer includes lithium cobalt oxide, a positive electrode dispersant, a positive electrode conductor and a positive electrode binder; wherein the positive electrode dispersant includes fluorinated acrylate rubber.
2. The positive electrode sheet according to claim 1, characterized in that: The positive electrode dispersant also includes hydrogenated nitrile rubber; preferably, the mass proportion of the hydrogenated segment in the hydrogenated nitrile rubber is 3-9%; and / or, the mass proportion of the fluorinated segment in the fluorinated acrylate rubber is 3-9%; and / or, the weight average molecular weight of the hydrogenated nitrile rubber is 10000-700000 g / mol; and / or, the weight average molecular weight of the fluorinated acrylate rubber is 5000-200000 g / mol.
3. The positive electrode sheet according to claim 2, characterized in that: The positive electrode dispersant is a combination of the hydrogenated nitrile rubber and the fluorinated acrylate rubber, and the mass ratio of the hydrogenated nitrile rubber to the fluorinated acrylate rubber is 1 to 20:
1.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The mass ratio of the lithium cobalt oxide, the positive electrode dispersant, the positive electrode conductive agent and the positive electrode binder is (96-99): (0.01-0.1): (0.5-1.5): (0.5~1.5)。 5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The lithium cobalt oxide is modified lithium cobalt oxide; Preferably, the preparation method of the modified lithium cobalt oxide comprises: Step S1, mixing raw materials including a first cobalt salt and a first aluminum salt, and then sequentially performing a first coprecipitation and a first heat treatment to obtain a first aluminum-doped cobalt tetroxide; Step S2, mixing the raw materials including the second cobalt salt and the second aluminum salt, and sequentially performing a second coprecipitation and a second heat treatment to obtain a second aluminum-doped cobalt tetroxide; Step S3, mixing the raw materials including the first lithium source, the first aluminum-doped cobalt tetroxide and the first additive and then performing a first calcination to obtain a first lithium cobaltate; Step S4, mixing the raw materials including the second lithium source, the second aluminum-doped cobalt tetroxide and the second additive and performing a second calcination to obtain a second lithium cobaltate; Step S5, mixing the raw materials including the first lithium cobalt oxide, the second lithium cobalt oxide and the third additive and performing a third calcination to obtain modified lithium cobalt oxide; Wherein, the median particle size of the first aluminum-doped cobalt oxide is 3-5 μm; and / or the median particle size of the second aluminum-doped cobalt oxide is 15-18 μm.
6. The positive electrode sheet according to claim 5, characterized in that: In the step S1, the mass ratio of the first cobalt salt to the first aluminum salt is 1:0.005-0.015; and / or, the temperature of the first coprecipitation is 25-45°C; and / or, the time of the first coprecipitation is 10-18h; and / or, the temperature of the first heat treatment is 600-800°C; and / or, the time of the first heat treatment is 4-8h; And / or, in step S2, the mass ratio of the second cobalt salt to the second aluminum salt is 1:0.005-0.015; and / or, the temperature of the second coprecipitation is 25-45°C; and / or, the time of the second coprecipitation is 10-18h; and / or, the temperature of the second heat treatment is 600-800°C; and / or, the time of the second heat treatment is 3-6h.
7. The positive electrode sheet according to claim 5 or 6, characterized in that: In the step S3, the mass ratio of the first lithium source, the first aluminum-doped cobalt oxide and the first additive is 1:(2.1-2.5):(0.005-0.01); and / or the first calcination temperature is 700-1000° C.; and / or the first calcination time is 6-10 hours; and / or, in the step S4, the mass ratio of the second lithium source, the second aluminum-doped cobalt oxide and the second additive is 1:(2.1-2.5):(0.005-0.01); and / or, the temperature of the second calcination is 700-900° C.; And / or, the second calcination time is 6 to 10 hours.
8. The positive electrode sheet according to any one of claims 5 to 7, characterized in that: In step S5, the mass ratio of the first lithium cobaltate, the second lithium cobaltate and the third additive is 1:(0.2-0.3):(0.005-0.01); and / or the temperature of the third calcination is 400-600° C.; and / or the time of the third calcination is 4-6 hours.
9. The positive electrode sheet according to any one of claims 5 to 8, characterized in that: The first additive and the second additive are each independently selected from any one or more of a first Mg source, a first Al source, a first Co source, a first Ti source, a first Zr source, a first Y source and a first La source; And / or, the third additive is selected from any one or more of a second Mg source, a second Al source, a second Ti source, a second Zr source, a second Y source, a second La source, a P source, a F source and a second Co source; Preferably, the first additive is a combination of the first Mg source and the first Y source, and the mass ratio of the first Mg source to the first Y source is 1:0.1-0.5; and / or, the second additive is a combination of the first Co source and the first Ti source, and the mass ratio of the first Co source to the first Ti source is 1:0.1-1; And / or, the third additive is a combination of the second Al source and the F source, and a mass ratio of the second Al source to the F source is 1:0.1-1.
10. A lithium ion battery comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The positive electrode sheet is the positive electrode sheet according to any one of claims 1 to 9.
Citation Information
Patent Citations
Electrode material, electrode plate, preparation method of electrode plate and secondary battery
CN115842128A
Non-aqueous electrolyte and lithium ion battery containing same
CN116190794A
Lithium ion battery, preparation method thereof, positive pole piece and power utilization device
CN118693331A
Composite positive electrode slurry, positive electrode and preparation method thereof
CN119133455A
Positive electrode current collector for rechargeable lithium battery, positive electrode, and rechargeable lithium battery including same
EP4394952A1